1985
DOI: 10.1148/radiology.157.3.4059548
|View full text |Cite
|
Sign up to set email alerts
|

Osseous lipoma: CT appearance.

Abstract: Characteristic radiographic and computed-tomographic (CT) features of seven cases of osseous lipoma are reported: six with medullary and one with parosteal locations. Radiological diagnosis of this lesion is discussed, with emphasis on potential pitfalls in interpretation of CT scans. Although the presence of fat-equivalent density on scans is highly suggestive of osseous lipoma, comparable attenuation is documented in cases of chronic osteomyelitis and postnecrotic subchondral excavation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0
3

Year Published

1987
1987
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(36 citation statements)
references
References 0 publications
1
32
0
3
Order By: Relevance
“…Parosteal lipomas represent 0.3% of all lipomas [37,38]. Parosteal lipomas occur most commonly between the 5th and 7th decades [39]. Parosteal lipomas are generally located upon the diaphyses of long tubular bones such as the femur, humerus, tibia, and proximal radius [40].…”
Section: Traumatic Atraumaticmentioning
confidence: 99%
“…Parosteal lipomas represent 0.3% of all lipomas [37,38]. Parosteal lipomas occur most commonly between the 5th and 7th decades [39]. Parosteal lipomas are generally located upon the diaphyses of long tubular bones such as the femur, humerus, tibia, and proximal radius [40].…”
Section: Traumatic Atraumaticmentioning
confidence: 99%
“…Parosteal lipomas may be considered as a separate group of rare benign lipomas affecting the bones, performing either in mandible, cervical vertebra or fibula (7,8). Parosteal lipomas are exceedingly rare benign lipomatous neoplasms located adjacent to the periosteum of bones.…”
Section: Discussionmentioning
confidence: 99%
“…In the long bones, intraosseous lipomas are found in the metaphyseal and diaphyseal regions. 2 The sex predeliction in their tumors is controversial. Some authors have reported an equal sex predilection while some others have reported a slight male preponderance.…”
Section: Discussionmentioning
confidence: 99%